Influences of azolla-derived biofertilizer and compost on soil chemical properties and rice growth in contaminated soil - Talaat R. El-beshbeshy; Asmaa Z. El Kady; Rania M. El Shal; Nazih Y. Rebouh; Mohamed S. Shokr; Naglaa E. Khalafallah (PLoS ONE, 2026)
Pollution caused by heavy metals and extensive use of synthetic fertilizers has harmful effects on soil organic matter content, soil health, environmental safety, and human health. To overcome these problems, using several types of amendments to improve soil conditions can boost crop productivity. It has been proposed to use Azolla as compost and a biofertilizer to enhance soil quality and promote rice growth in contaminated soil. This study was carried out at the Department of Soil and Water, Faculty of Agriculture, Tanta University, Egypt, during summer season of 2021. To investigate the effect of Azolla in two forms: as a green manure ( Azolla pinnata ) and as compost under different levels of nitrogen fertilizer on the growth of the rice crop (Sakha 104). In addition, the study investigated some soil chemical properties contaminated by heavy metals such as Cu, Pb, and Zn. To achieve the aim of this study, soil samples from two different sites were collected from Kafr El-Zayat, Gharbia Governorate, Egypt. Thirteen treatments were used to fulfill the study's objectives. The results showed that the application of Azolla pinnata and Azolla compost significantly improved the grain production of rice, increased cation exchange capacity (CEC), % of organic matter (OM), available and total NPK, and prevented the pH from rising. The total and available levels of Zn and Cu in our samples dropped to an acceptable level, leading to the adoption of remedial measures according to Canadian soil quality recommendations, although the total Pb content remained high. In the end, our research advances important Sustainable Development Goals (SDGs) of the United Nations, such as Life on Land (SDG 15) by restoring soil health, Responsible Consumption and Production (SDG 12) by encouraging circular bioeconomies, and Zero Hunger (SDG 2) and Good Health (SDG 3) through safer food production.